The Role and Responsibilities of a Notary in the Deed of Inheritance Renunciation and Its Impact on Creditor Protection: An Islamic Law Perspective - Chetya Dwi Mandasari; Tahegga Primananda Alfath; Heru Kuswanto (Universitas Ibn Khaldun, 2026)
This study aims to analyze the role and responsibilities of notaries in drafting deeds relating to the renunciation or transfer of inheritance rights, and to examine their implications for creditor protection under civil and Islamic law. A normative juridical method was employed, utilizing statutory, conceptual, case-based, comparative, and fiqh mawaris approaches. The findings establish a fundamental distinction between renunciation of inheritance (verwerping van erfenis) under Article 1057 of the Indonesian Civil Code—which falls within the court's jurisdiction—and the transfer of inheritance rights formalized through notarial deeds under contractual freedom. Within Islamic inheritance law, the relevant concepts are not renunciation of inheritance but rather takharuj (التخارج) and tashaluh (التصالح), which are mechanisms for the consensual transfer of inheritance rights after such rights have vested, pursuant to the principle of ijbari. With respect to creditor protection, Islamic law explicitly prioritizes the settlement of debts over the distribution of inheritance, as stipulated in Surah An-Nisa verses 11–12, so that no agreement among heirs may lawfully prejudice the rights of legitimate creditors. Indonesian civil law, by contrast, continues to rely on repressive mechanisms such as actio pauliana under Article 1341 of the Civil Code and Article 1061, which have not provided adequate preventive protection. Comparative analysis with Dutch law (beneficiaire aanvaarding) and French law (renonciation à succession) underscores the need for comprehensive reform of Indonesian inheritance law. This study recommends strengthening notarial professional standards, developing more comprehensive regulations, and harmonizing Islamic inheritance principles with civil law within Indonesian notarial practice. Keywords: Notary; Inheritance Renunciation; Takharuj; Creditor Protection; Islamic Inheritance Law